Doing Industry 4.0 – participatory design on the shop floor in the view of engineering employees - Pfeiffer, Sabine; Lee, Horan; Held, Maximilian (Cuadernos de Relaciones Laborales, 2019)
Industry 4.0 features a cluster of diverse technologies. Implementing these in the enterprise will require a considerable amount of participation. Current forms of participatory design (Agile methods, design thinking, open innovation) more closely involve customers, but not generally the company’s own production workers. We investigate if and how the production engineers who will implement Industry 4.0 want to involve their colleagues on the shop floor. We present results of qualitative interviews, a quantitative survey and Q-sorts conducted with around 230 engineering employees of an automotive plant. Participating engineers were invited to express their viewpoints, experiences and visions on how production workers could be involved in the implementation of Industry 4.0. On the one hand, the data suggest positive attitudes towards, and experiences of participation. On the other hand, participation is demanding: respondents report a lack of time and opportunities. It may require more imagination and initiative to break through existing formal processes often restricted to “catch-up” improvements.
Keywords: Participation; engineering; innovation; Industry 4.0.